Evaluation of the Global Comparative Study on Tenure; Uganda Case Study - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
The GCS project in Uganda sought to examine the relationship between statutory and customary land tenure and how these relationships affected the tenure security of forest -dependent communities, particularly women, youth and other marginalized groups. Through a transdisciplinary research effort, the GCS produced new information, analysis and tools that were directly relevant to policymakers, practitioners and forest -dependent communities.